Eventos de grande diminuição da coluna total de ozônio sobre o Sul do Brasil: estudo da dinâmica estratosfera-troposfera com o modelo WRF - Rodríguez, Lissette Guzmán (2021)
The increase of ultraviolet solar radiation that reaches the Earth’s surface as a consequence of the decrease in the total ozone column has a negative impact on human health. Ozone depletion events that affect southern Brazil in the spring have been extensively studied. However, large depletion of the total ozone column can occur throughout the year, responding to different mechanisms. Throughout the year and even without evident isentropic transport of air masses from a region of low total ozone column, the cyclonic anomalies of potential vorticity of sub-synoptic scale have shown to be able to locally reduce the ozone mixing ratio by vertical stretching the air parcels between isentropic surfaces, leading to a decrease the total ozone. In the present work, the temporal and spatial variability of total ozone and the ozone mixing ratio in the city of Santa Maria was analyzed using ERA-5 reanalysis data, in the 1979-2019 period. The seasonal cycle of the total ozone column of maximum in spring and minimum in autumn was confirmed. There were 116 atypical depletion events of the total ozone column identified, with total ozone column values in Santa Maria below the monthly mean minus 2.5 times the monthly standard deviation. For better analysis and representation of the dynamic structures and processes involved, the events were simulated with the Weather Research and Forecasting mesoscale model. Mean seasonal synoptic patterns showed important structures for depletion events at tropospheric and stratospheric levels, later confirmed in the analysis of five specific cases: in winter and spring, a stratospheric trough delimited the region of negative total ozone column anomalies and favored the isentropic transport of air masses from the Antarctic ozone hole region to Santa Maria. In summer, the region of strong difluence at the edge of Alta de Bolivia at the equatorial entrance of the subtropical jet streak enabled the lifting of the dynamic tropopause and the mixing of tropospheric air into the lower stratosphere. In autumn, a combination of cyclonic anomalies at 20 hPa and anticyclonic anomalies at 50 hPa isobaric level, led to major ozone depletion, with a total ozone column below 210 DU over the continent and ozone mixing ratio negative anomalies at stratospheric levels. The position and strength of the tropospheric jets were key in setting the regions of the biggest negative (positive) total ozone column anomalies at the equatorial (polar) entrance of the jet streak, due to the effect of transverse circulation in the tropopause folds and the predominant upward (downward) mass fluxes in those regions.